2011
DOI: 10.1590/s0103-50532011000200021
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive determination of acetaminophen in pharmaceutical preparations and biological samples using multi-walled carbon nanotube modified glassy carbon electrode

Abstract: Um eletrodo quimicamente modificado foi construído, baseado em eletrodo de carbono vítreo modificado por nanotubos de carbono de paredes múltiplas (ECV-NTCPM). O uso deste sensor na determinação de acetaminofeno (ACT), em meio aquoso tamponado, foi demonstrado. As medidas foram realizadas com utilização dos métodos de voltametria de pulso diferencial (VPD), voltametria cíclica (VC) e cronoamperometria (CA). A aplicação de VPD mostrou dois intervalos dinâmicos lineares. O primeiro intervalo dinâmico linear foi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Fig. Referring to the analytical performances of some recently published reports [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] (Table 2), it is found that the obtained detection limit in this work is lower than other modified electrodes, which is likely related that MWCNT-CTAB have high electrocatalytic and surface area effects. 6(b)).…”
Section: Linearity Range and Detection Limit Using Voltammetrymentioning
confidence: 66%
“…Fig. Referring to the analytical performances of some recently published reports [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] (Table 2), it is found that the obtained detection limit in this work is lower than other modified electrodes, which is likely related that MWCNT-CTAB have high electrocatalytic and surface area effects. 6(b)).…”
Section: Linearity Range and Detection Limit Using Voltammetrymentioning
confidence: 66%
“…The subtle electronic behavior of CNTs reveals that they have a high electrocatalytic effect when used as an electrode [2]. Recently, a carbon nanotube-modified solid electrode has attracted much attention because of its excellent electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Nyquist plots were obtained when the CPEs were modified with PEA, PEA/MWCNT 2 wt.%, 3 wt.%, and 5 wt.% and immersed in a 0.1 M KCl solution containing both 5 mM of K 3 [Fe(CN) 6 ] and K 4 [Fe(CN) 6 ]. The semicircle diameter of EIS is considered to be equal to R ct (charge transfer) in Nyquist diagram . Accordingly, the results showed that the diameter of the semicircle for the CPE modified with PEA/MWCNT 5 wt.% was smaller than that of the CPE modified with PEA/MWCNT 2 and 3 wt.% (Figure ).…”
Section: Resultsmentioning
confidence: 97%